REPRODUCTIVE BIOLOGY OF RAZOR CLAM SOLEN THACHI COSEL, 2002 AT THUY TRIEU LAGOON - KHANH HOA - Hoang, Do Huu; Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2016)
Razor clam Solen thachi Cosel, 2002 is one of the high valuable species distributed at Thuy Trieu lagoon, Khanh Hoa. The aim of this paper was to examine some reproductive biology characteristics of razor clam. Samples of razor clam were collected monthly with a total of 822 inds. at Thuy Trieu lagoon and analysed at the laboratory of the Institute of Oceanography. Results of analysis showed that sex ratio was about 1:1. Spawning season was mainly between December and March of the following year, with the peak in December. The absolute fecundity was 1,048,893 ± 608,964 eggs per individual, while the relative fecundity was 146,349 ± 95,666 eggs/gram of body weight. Length of the first maturity was recorded at 69.6 mm of shell length. This paper provided baseline data for management and sustainable exploitation of marine living resources.